Multiculturalism as a globalizing challenge to local cultural identities and heritages - Šabec, Ksenija (Teorija in praksa, 2014)
The article proceeds from two theses: that the protection of local cultural identities and heritages as a method for maintaining and even enhancing local (and also national) cohesion in the face of globalizing challenges is sensible and justified only under the condition that the cultural heritage is constructed on the basis of multiculturalism, and the intertwinement and interaction between diverse various local lifeworlds; and that (re)constructed local (territorial) cultures and identities cannot be completely captured by binary and oversimplified definitions of old and new localisms. Both of these theoretical premises are with the help of structured and semi-structured interviews applied to a case study of the cultural, potentially economic, political, and social transformation of specific local, territorial, and cultural identities in the town of Idrija, Slovenia, as a geographically remote and delineated "hill" town with a specific cultural, natural, and technical (industrial) tradition and heritage. The value of its very specific heritage was recognized by its successful inscription in 2012 to the list of UNESCO World Heritage sites as an example of institutional and symbolic global proximity and presence.
Keywords: cultural heritage; Cultural identity; Cultural property; Globalizacija; Globalization; Kulturna dediščina; Kulturna identiteta; lokalna identiteta; Multiculturalism; Multikulturalizem; večkulturnost